Magnetic susceptibility and properties of Alisols under forest and crops in south Amazonas - Brito, Wildson Benedito Mendes; Campos, Milton César Costa; Souza, Fernando Gomes de; Silva, Laércio Santos [UNESP]; Lima, Hedinaldo Narciso; Lima, Alan Ferreira Leite de; Cunha, José Maurício da (Elsevier, 2024)
Anthropic actions have motivated pieces of research on the impacted naturally poor soils of the Brazilian Amazon, requiring the use of diagnostic attributes that are increasingly specific to each environmental change. The use of magnetic proxies inherent in the soil may be the key to understanding the changes that occur in the soil and the environment. Therefore, this study aimed to characterize the physical, chemical and mineralogical properties of Alisols, in addition to determining the intensity and origin of the magnetic signal for future calibrations as an environmental proxy for monitoring soil fertility. One natural and three cultivated Alisols were sampled using systematic meshes in three layers: 0–5, 5–10 and 10–20 cm. The natural Alisol is a tropical forest and the agricultural ones refer to the cultivation of annatto, cupuaçu and guarana. A total of 192 samples/area were submitted to physical, chemical, mineralogical and magnetic susceptibility (MS) analysis. MS measured at low and high frequency and converted to specific mass (χlf and χhf), then descriptive, univariate and multivariate statistical analyzes were applied to the results. The conversion of the physically good and chemically poor and acidic natural Alisols to agricultural crops, caused an increase in the density and amplitude of the pH in water and Al3+ of the soil, plus a reduction in macroporosity, gravimetric humidity, available phosphorus and iron oxalate contents, and the incorporation of organic carbon in depth. All Alisols showed low χlf and χhf. However, χlf values decreased in depth for cultivated Alisols (0.53–0.26 x 10−6 m3 kg−1), whereas, for natural Alisol, these values tended to increase towards the subsurface (0.21–0.23 x 10−6 m3 kg−1). Nevertheless, the value of χlf and χhf were highly representative within the cultivation areas, which was characterized as a suitable proxy to monitor the fertility of the Alisols in the Amazon region.
Keywords: Agricultural conversion; Alisols; Iron oxides; Magnetic signal; Proxy